New Direction in Antimicrobial Delivery System: Preparation and Applications of Hydrogel Microspheres - Jiapeng Li; Guotao Wei; Yihao Yuan; Ling Wang; Miaohan Qiu; Bo Li; Ruofei Ma; Jiawei Wu; Ziyi Shen (Pharmaceutics)
Antimicrobial delivery systems have undergone extensive development, yet conventional carriers still exhibit limitations such as low loading capacity, inadequate controlled release mechanisms, and cytotoxicity. Recent studies have increasingly demonstrated the potential of Hydrogel Microspheres (HMSs) for antimicrobial delivery. These microspheres exhibit small dimensions, high drug-loading capacity, and the ability to achieve deep-targeted delivery, complemented by adjustable physicochemical properties and biocompatibility that create favorable conditions for antimicrobial transportation. This review systematically examines HMS preparation strategies, characteristic properties, transported antimicrobials, and therapeutic applications. Particular emphasis is placed on critical preparation parameters governing HMS performance, especially those influencing drug delivery dynamics. We conclude by addressing current challenges and proposing actionable strategies for material optimization and clinical translation. This work aims to advance HMS-based antimicrobial delivery systems for more effective infection control.